Segregated behind the walls: residential patterns in pre-industrial Copenhagen. (2nd October 2019) - Perner, Mads Linnet
ABSTRACT: This article presents a longitudinal study of residential patterns in the fortified city of Copenhagen. It uses a Geographical Information System (GIS) approach along with the HISCO and HISCLASS coding schemes for occupational titles to discuss residential segregation in Copenhagen between 1711 and 1845. In a period of population growth, spatial expansion of Copenhagen was prevented by building restrictions related to the fortress. As the city grew increasingly dense into the eighteenth and nineteenth centuries, historians have assumed that distinct areas of high or low social status (horizontal segregation) were non-existent and that the city was only socially stratified within buildings (vertical segregation), with basements and attics housing the economically deprived. Already in the early eighteenth century, however, the social landscape of Copenhagen was divided into areas of high and low status. Further, towards the middle of the nineteenth century, social status increased in the city centre as it decreased in peripheral areas. This change stands in contrast to the models of Sjoberg and Vance, in which socio-geographical change comes with urban expansion. Instead, I argue that fires and other disasters offered similar opportunities for change, with the extent of socio-geographical change determined by the political circumstances surrounding reconstruction.